Atrial fibrillation in amyloidotic cardiomyopathy: prevalence, incidence, risk factors and prognostic role. (September 2015) - Longhi, Simone; Quarta, Candida Cristina; Milandri, Agnese; Lorenzini, Massimiliano; Gagliardi, Christian; Manuzzi, Lisa; Bacchi-Reggiani, Maria Letizia; Leone, Ornella; Ferlini, Alessandra; Russo, Antonio; Gallelli, Ilaria; Rapezzi, Claudio
Abstract Background: Although atrial fibrillation (AF) is a known complication of amyloidotic cardiomyopathy (AC), a precise pathophysiological and prognostic characterization is not available. We therefore aimed to assess prevalence, incidence, risk factors and prognostic significance of AF in light-chain (AL), hereditary transthyretin-related (m-ATTR) and non-mutant transthyretin-related (wt-ATTR) AC. Methods: Retrospective study of 262 patients with AC (123 AL, 94 m-ATTR, 45 wt-ATTR) from a single center. Results: AF prevalence was 15% (AL 9%, m-ATTR 11%, wt-ATTR 40%). During a median follow-up of 1.2 years 11 patients developed AF (2.1% person-years). Age, heart failure (HF), left ventricular (LV) ejection fraction, renal involvement, left atrial size and right atrial pressure were independently associated with AF. AF was associated with incident HF but not with increased mortality. All AF patients were prescribed warfarin and none suffered thromboembolic events. Conclusions: In AC the prevalence of AF varies widely according to etiology with a mean value of 15% that reaches 40% in wt-ATTR amyloidosis. Age, HF, LV ejection fraction, left atrial size and right atrial pressure were the main independent risk factors, while wall thickness and etiology were not the main independent risk factors. AF does not seem to impact all-cause mortality but was strongly associated with prevalent and incident HF.